Handbook of behavioral and cognitive geography - Montello, Daniel R. 1959- (Cheltenham, United Kingdom EE Edward Elgar Publishing, 2018)
This comprehensive Handbook summarizes existing work and presents new concepts and empirical results from leading scholars in the multidisciplinary field of behavioral and cognitive geography, the study of the human mind, and activity in and concerning space, place, and environment.
Includes bibliographical references and index.
Keywords: Human geography; Residential mobility; Migration, Internal -- Social aspects